2021
DOI: 10.1186/s10194-021-01240-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered amygdala effective connectivity in migraine without aura: evidence from resting‐state fMRI with Granger causality analysis

Abstract: Background Granger causality analysis (GCA) has been used to investigate the pathophysiology of migraine. Amygdala plays a key role in pain modulation of migraine attack. However, the detailed neuromechanism remained to be elucidated. We applied GCA to explore the amygdala-based directional effective connectivity in migraine without aura (MwoA) and to determine the relation with clinical characteristics. Methods Forty-five MwoA patients and forty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…The study revealed that the SVM classifier demonstrated predictive ability with an accuracy of more than 89%, treating abnormal amygdala-related FC patterns and clinical characteristics as features of interest. The present study demonstrated that the amygdala showed stronger FCs with some higher cognitive regions, including the limbic system, visual cortex and prefrontal cortex in MwoA patients compared to the HCs, consistent with previous studies ( Wei et al, 2020b ; Huang et al, 2021 ). The higher cognitive regions are involved in the top-down pain control circuit.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study revealed that the SVM classifier demonstrated predictive ability with an accuracy of more than 89%, treating abnormal amygdala-related FC patterns and clinical characteristics as features of interest. The present study demonstrated that the amygdala showed stronger FCs with some higher cognitive regions, including the limbic system, visual cortex and prefrontal cortex in MwoA patients compared to the HCs, consistent with previous studies ( Wei et al, 2020b ; Huang et al, 2021 ). The higher cognitive regions are involved in the top-down pain control circuit.…”
Section: Discussionsupporting
confidence: 93%
“…The amygdala, a core region of the neurolimbic system, plays a crucial role in regulating the top-down nociceptive pathway ( Maizels et al, 2012 ; Minen et al, 2016 ). On the one hand, seed-based whole-brain functional connectivity (FC) and Granger causality analyses revealed that migraine sufferers exhibit aberrant connectivity between the amygdala and the higher cortex ( Wei et al, 2020b ; Huang et al, 2021 ). On the other hand, some studies suggested recurrent nociceptive input could affect the anatomical pattern of the amygdala, and these changes may explain the functional abnormalities in migraine patients ( Jia and Yu, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was possible that the identified temporal latency alteration of the STG/MTG may be related to sound hypersensitivity and disrupted salience response in patients with migraine. Our findings were partially supported by recent resting-state functional MRI studies that show aberrant effective connectivity of the STG/MTG [47] and sensorimotor cortex [48] in migraine patients. Furthermore, the absence of significant differences in STG/MTG and PoCG/PreCG lags between the two migraine groups indicated that atypical propagation of intrinsic activity in these two sensory processing-related brain regions were common features of individuals suffering from EM and CM.…”
Section: Discussionsupporting
confidence: 85%
“…In addition to NAc and mPFC, amygdala and hippocampus-both major nodes of the limbic brain ( 7 )-have been directly implicated in chronic pain conditions. Hence, amygdala functional connectivity is consistently altered in migraine patients ( 113 115 ). Amygdala volume and shape on the other hand are altered in CLBP patients ( 116 , 117 ).…”
Section: Beyond Sensory Perception: Chronic Pain and Aversive Learning A Conceptualization In Briefmentioning
confidence: 99%